Metode Kuadrat Terkecil Untuk Meramalkan Tingkat Likuiditas Pada BMT Kapuas Mandiri Sejahtera Di Kota Pontianak - Syaifullah, Muhammad; Fachrurazi, Fachrurazi; Anwari, Muhammad Khairul; Agriani, Dian (Universitas Islam Negeri Alauddin Makassar, 2019)
The aimed of this research is due to the existence of accounting information related to liquidity problem in Baitul Maal wa Tamwil/The house of Business and Social (BMT) â€œKapuas Mandiri Sejahteraâ€ by determining the liquidity ratios and liquidity analysis through the least square trend method analysis. Therefore, we employ the secondary data sources in the form of financial statements. The result is that the 2013 Cash Ratio is less liquid, 2014 (liquid), 2015 (illiquid), 2016 (quite liquid), and 2017 is liquid respectively. Financing to Deposit Ratio (FDR) ratio in 2013 and 2017 (liquid), 2014 and 2016 (quite liquid), and ultimately in 2015 (less liquid). Next, The results of the least square quadrant method analysis, namely the cash ratio from 2013-2017 has depicted that BMT's cash ability to generate income fluctuated with a downward trend. As for FDR ratio from 2013-2017, the ability of financing to generate income has fluctuated whereby the trend has experienced a declining from year to year.Keywords: cash ratio, financing to deposit ratio, liquidity ratioÂ Adanya informasi akuntansi terkait likuiditas bermasalah di Baitul Maal wa Tamwil (BMT) Kapuas Mandiri Sejahtera. Artikel ini mengulas tingkat rasio likuiditas dan analisis rasio likuiditas. Sumber data sekunder berupa laporan keuangan. Pengumpulan data dengan teknik dokumentasi. Analisis data dengan analisis likuiditas dan trend metode kuadrat terkecil. Hasil yang temukan bahwa cash ratio tahun 2013 (kurang likuid), tahun 2015 (tidak likuid), tahun 2014 (likuid), tahun 2016 (cukup likuid) dan tahun 2017 (likuid). Rasio FDR tahun 2013 dan 2017 (likuid), tahun 2014 dan 2016 (cukup likuid), tahun 2015 (kurang likuid). Hasil analisis Metode Kuadrat Terkecil yaituÂ cash ratio dari tahun 2013-2017 kemampuan kas di BMT dalam menghasilkan pendapatan mengalami fluktuasi. Dengan trend metode kuadrat terkecil, kas memiliki kecenderungan menurun dari tahun 2013-2017. Rasio FDR dari tahun 2013â€“2017, kemampuan pembiayaan dalam menghasilkan pendapatan mengalami fluktuasi. Analisis trend metode kuadrat terkecil menunjukkan bahwa pembiayaan memiliki kecenderungan menurun dari tahun 2013-2017.Kata Kunci: Rasio Kas, Rasio Pembiayaan, Rasio Likuiditas.